Influence of friends on undergraduates "Liking" behavior on facebook pages. - Chee, Ting Feng. (2013)
This study aims to find out about Facebook users’ “Liking” behaviour on Facebook brand Pages. This research studies on an individual’s tie strengths with his friends, his level of interest in the brand and the influence of crowd joining behaviour in enhancing the propensity to “Like” the brand Page.